Implementation of Modified SEPIC Converter for Renewable Energy Built DC Microgrids - B. Jyothi; P. Bhavana; B. Thirumala Rao; Mukesh Pushkarna; null Kitmo; Repele Djidimbele (International Journal of Photoenergy)
The nonavailability of fossil fuels and the shortcomings of nonconventional energy sources taking place in the environment lead the research and development towards alternative and clean energy sources such as renewable energy sources. Renewable or nonconventional energy resources are being used to meet ever-increasing energy demand. The photo voltaic (PV) energy is the right choice of renewable energy for small voltage DC distribution systems, due to their advantages. But this energy source can produce low output power at the utility grid. Hence, to step up this low input voltage to high value for a range of high-voltage applications, DC-DC converters are integrated to the DC microgrids by means of PV system. The present work elaborates the modified SEPIC converter (MSC) designed based on the traditional SEPIC with a boost-up module. In comparison with conventional or traditional SEPIC converter, the proposed MSC produces high voltage gain and continuous current to the DC microgrids. Furthermore, MSC is operated with only one controlled switch. The proposed converter design improves the efficiency, output voltage, and continuous output current of the DC microgrids. This entire work is completed with PSIM, and finally, numerical simulation results prove the possibility of the MSC with PV-powered DC microgrids, and also the dynamic response of MSC for DC microgrid loads enhances the regulated output voltage and continuous output current of DC loads.